Inventory simulation-optimization model for small business - Yudhia Mulya (Research Collaboration Community (RCC), 2020)
Simulation-optimization inventory models are widely used in inventory management studies, including for perishable good. A good inventory management is required to save inventory cost. We use simulation approach to take into consideration of uncertain demand and lead time to obtain a better result of optimal order quantity that minimizes inventory cost. Simulation result shows that simulation-optimization models generates lower total inventory cost. The simulation provides information of objectives in inventory management: (1) how much to order and (2) when to order with minimum cost which gives valuable information in business decision making.